Identificação e Quantificação por DAD-HPLC, da Fracção Fenólica Contida em Folhas de Quercus suber L. - Evaristo, Isabel Maria; Leitão, Maria Cecília (Silva Lusitana, 2001)
In this study, an analytical method has been developed for the determination of phenolic compounds since they are related with disease and pests plant resistance mechanisms. The components of the hydrolysed extract (gallic acid, ellagic acid, catechin, epicatechin, caffeic acid, p-coumaric acid and ferulic acid) have been resolved and identified by DAD-HPLC based on their retention times and spectral data. For quantifications, the external standard method was used.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: avoir un rôle important; caffeic acid; car ces; catechin; dans la présente étude; défense des; des feuilles de chêne; détermination des composés phénoliques; ferulic acid; gallic acid; liège; méthode analytique pour la; on a developpé une; p-coumaric acid; Quercus Suber L; résumé; substances sont susceptibles d; sur les mécanismes de

Identificação e Quantificação por DAD-HPLC, da Fracção Fenólica Contida em Folhas de Quercus suber L. (Silva Lusitana, 2001)
In this study, an analytical method has been developed for the determination of phenolic compounds since they are related with disease and pests plant resistance mechanisms. The components of the hydrolysed extract (gallic acid, ellagic acid, catechin, epicatechin, caffeic acid, p-coumaric acid and ferulic acid) have been resolved and identified by DAD-HPLC based on their retention times and spectral data. For quantifications, the external standard method was used.